Nanoemulsion and Encapsulation Strategy of Hydrophobic Oregano Essential Oil Increased Human Prostate Cancer Cell Death via Apoptosis by Attenuating Lipid Metabolism - Haribalan Perumalsamy; Rajeshkumar Shanmugam; Jun-Ran Kim; Gokulanathan Anandapadmanaban; Md. Amdadul Huq; Kamal Dua; Dinesh Kumar Chellappan; Tae Hyun Yoon; Sri Renukadevi Balusamy (Bioinorganic Chemistry and Applications)
Origanum vulgare essential oil (EO) is traditionally well-known for its aromatic properties and biomedical applications, including anticancer. This was the first report where oregano essential oil-based nano emulsion (OENE) was synthesized for studying its effects on prostate cancer cell lines (PC3). At first, we have synthesized OENE and characterized using various spectroscopic analyses. The toxicity and inhibitory concentration (IC50) of OENE toward prostate cancer by MTT analysis were performed. The lipid biogenesis mediated, molecular target pathway analyses were performed using fluorescence cellular staining techniques, real-time RT-PCR, or western blotting analysis. OENE showed IC50 at 13.82 µg/mL and significantly induced distinct morphological changes, including cell shrinkage, cell density, and cell shape reduction. In addition, OENE could also significantly decreased lipid droplet accumulation which was confirmed by studying mRNA transcripts of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) (0.31-fold), fatty acid synthase (FASN) (0.18-fold), and sterol regulatory element-binding protein (SREPB1) (0.11-fold), respectively. Furthermore, there is a significant upregulation BAX (BCL2 associated X) and caspase 3 expressions. Nevertheless, OENE decreased the transcript level of BCL2 (B-cell lymphoma 2), thus resulting in apoptosis. Overall, our present work demonstrated that OENE could be a therapeutic target for the treatment of prostate cancer and warrants in vivo studies.